Arduino for dummies - Nussey, John (--For dummies., 2013)
Whether you're an artist, designer, programmer or hobbyist, Arduino lets you learn about and play with electronics. Discover how to build a variety of circuits that can sense or control real-world objects, prototype your own product, and even create interactive artwork.